2022
DOI: 10.1371/journal.pone.0264327
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of safety and efficacy of endovascular aneurysm repair in aneurysm patients with severe angulated infrarenal neck

Abstract: Objectives A growing number of abdominal aortic aneurysms with severe angulated neck anatomy is treated by endovascular means. However, contradictory early and late outcomes have been reported. Our review and outcome analysis attempted to evaluate the available literature and provide clinicians with a base for clinical implementation and future research. Materials and methods A systematic review of the literature was undertaken to identify the outcomes of endovascular aneurysm repair in patients with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Late onset EL1A is an uncommon complication after EVAR, with an incidence of 1-5%. [22][23][24] It is associated with continued sac expansion and risk of rupture. 25,26 There are studies which suggest that primary EL1A, defined as EL1A at the completion angiography, has a more mild course when compared to late onset EL1A.…”
Section: Discussionmentioning
confidence: 99%
“…Late onset EL1A is an uncommon complication after EVAR, with an incidence of 1-5%. [22][23][24] It is associated with continued sac expansion and risk of rupture. 25,26 There are studies which suggest that primary EL1A, defined as EL1A at the completion angiography, has a more mild course when compared to late onset EL1A.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center study in Greece by Karathanos et al found that 34 of 317 EVAR patients (10.7%) had a neck angle >60°. 9 EVAR with severe neck angulation compared to non-severe neck angulation was associated with a significantly higher rate of type 1a endoleak until 3 years (5.6% vs 2.6%; p<0.00001; OR 2.57 95% CI 1.62-4.07), neck-related secondary procedure until 3 years (13.1% vs 9%; p<0.05; OR 1.42 95% CI 1.04-1.96), migration rates until 1 year (5.4% vs 4.0%; p<0.05; OR 1.41 95% CI 1.03-1.94), aneurysmrelated and all-cause mortality until 1 year (6.4% vs. 4.3%; p<0.05; OR 1.51 95% CI 1.16-1.98), but not related to aneurysm sac increase and rupture. 10 High-tortuosity neck in TEVAR also has its problem related to a significantly higher proportion of endoleaks, a potential risk factor for proximal stent-graft collapse or infolding, renal failure, stroke, longer operation time, and lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Two suprarenal platforms are approved for up to 75 degrees: the Treovance ™ (Terumo Aortic, Sunrise, FL, USA) and the Endurant II ™ (Medtronic Cardiovascular, Santa Rosa, CA, USA) systems. The infrarenal systems Anaconda ™ (Terumo Aortic, Glasgow, UK), Aorfix ™ (Lombard Medical, Didcot, UK), and the Conformable Excluder C3 device ™ (WL Gore & Associates, Flagstaff, AZ, USA) extend their IFU up to 90 degrees [ 25 ]. Midterm data for the Aorfix device show promising results, demonstrating no difference in sac expansion or regression in necks ≥ 60 degrees [ 26 ].…”
Section: Hostile Neck Characteristicsmentioning
confidence: 99%